ANALISIS DETERMINAN TINGKAT KEMISKINAN DI KABUPATEN SUMBAWA - Fifi Nurulita; K Kamaruddin; A Asmini (Jurnal Ekonomi & Bisnis, 2023)
This research aims to study the determinants of poverty levels in Sumbawa Regency which consist of economic growth, human development index and unemployment, both partially and simultaneously. The type of this research is causal associative with a quantitative approach. The type of data used is a quantitative obtained from secondary sources using the documentation method. The data that has been collected will be processed using the SPSS program for further study using techniques, including multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determining the coefficient of determination (R2). The results of the data analysis show that partially economic growth and the human development index have no effect on the poverty rate in Sumbawa Regency, while unemployment has a negative and significant effect on the poverty rate in Sumbawa Regency. Simultaneously, economic growth, human development index, and unemployment have a significant effect on the poverty rate in Sumbawa Regency. The ability of the variables of economic growth, human development index, and unemployment to vary changes in the poverty rate variable in Sumbawa Regency is 82.5%, while the remaining 17.5% is influenced by other variables outside this research model, such as education that is too low, lazy to work, limited natural resources, limited employment opportunities, limited capital, and family burdens.